IRAQ YESTERDAY, IRAQ TODAY (Journal of the College of Basic Education, 2023)
AbstractThis study intends to shed some light on why Iraq has been in the newsquite a bit, and why it has come to play the role it has in world affairs ofthe late twentieth and early twenty-first centuries. It concerns Iraqyesterday and today.IntroductionThe paper makes one simple assumption: the notion that all human life onthis planet – Muslim and non-Muslim, female and male, civilian andmilitary, poor or rich, ‘North’ or ‘South’, white or black– carries exactlythe same intrinsic worth. This essential value of human life is due to thepresence of the Divine spirit in all of humanity, the same spirit that,according to the Qur’an, God breathed into each and every human being[Qur’an 15:29 and 38:72]. From this premise of the worth and dignity ofeach and every human life and the right of each community to realizetheir vision of prosperity, dignity and righteousness, as long as that visiondoes not come at the expense of any other community, the researcherintends to begin this study. The paper is divided into two parts, the first concerns Iraq before thewar of 2003 – referred to in this study as Iraq yesterday; the second parttackles a number of current issues and attempts to find answers for somecontroversial questions including: What are the causes and consequencesof the US war on Iraq and the occupation of this country? Is it invasion orliberation? Is it true that post-war excuses for invasion and occupation areto make Iraq a western-style democracy and to spread Western values oris the US actually putting on a terrifying show for the whole world to seeand yield? And eventually where is the value of human life?